Atividade anticoccidicida de produtos naturais contra eimeria de caprinos - MORAES, Elinalva da Silva (2019)
Eimeriosis or coccidiosis is a frequent goat disease caused by protozoa of the genre Eimeria, responsible for significant economic losses in goat production. The control is performed with chemotherapeutic agents, which can leave residues in meat and milk and which can induce the resistance of the parasite. In this sense, the use of natural plant products can become an alternative for the control of Eimeria. The effect of the essential oils of Lippia gracilis and lectins has been shown in several studies applied to animal production, however, their effects on Eimeria are still little known. Considering the need for the development of technologies for animal health management using the native flora of the region, the objective of the present study was to evaluate the effect of L. gracilis, monoterpenes and lectin isolated from Canavalia brasiliensis (ConBr) essential oil on Eimeria de goat Different concentrations of essential oil of L. gracilis and monoterpenes carvacrol, p-Cimeno and γ-Terpineno were analyzed for viability of Eimeria spp. oocysts and a study was performed to analyze the viability of E. arloingi sporozoites under ConBr lectin action. The analyzes showed that L. gracilis essential oil genotype 201 presented LC50 of 4.56 mg/mL against oocysts and genotypes 108 and 109 destroyed 44.3% and 34.8% of oocysts when submitted to 10 mg/mL. Inhibition of oocyst sporulation by carvacrol was observed at an inhibitory concentration (IC50) of 0.42 mg/mL (95% CI 0.35-0.50; R2 0.97) and oocyst destruction resulted in lethal concentration (LC50) 0.963 mg/mL (95% LC 0.87-1.07; R2 0.97), with increased destruction of oocysts to a concentration of 7.0 mg/mL with 9.92% viable oocysts. The p-Cimeno and γ-Terpineno monoterpenes were not effective when analyzed separately. C. brasiliensis lectin protein had a lethal concentration (LC50) of 0.167 mg / mL (95% LC 0.10-0.27; R2 0.67) for E. arloingi sporozoites. The present work is the first one using L. gracilis essential oil, monoterpenes and C. brasiliensis lectin (ConBr) on Eimeria oocysts and sporozoites isolated from small ruminants in destruction, inhibition of oocyst sporulation and inhibition of viability of E. arloingi sporozoites.